EAACI IG Biologicals task force paper on the use of biologic agents in allergic disorders. Issue 7 (24th April 2015) - Boyman, O.; Kaegi, C.; Akdis, M.; Bavbek, S.; Bossios, A.; Chatzipetrou, A.; Eiwegger, T.; Firinu, D.; Harr, T.; Knol, E.; Matucci, A.; Palomares, O.; et al.
Abstract Biologic agents (also termed biologicals or biologics) are therapeutics that are synthesized by living organisms and directed against a specific determinant, for example, a cytokine or receptor. In inflammatory and autoimmune diseases, biologicals have revolutionized the treatment of several immune‐mediated disorders. Biologicals have also been tested in allergic disorders. These include agents targeting IgE; T helper 2 (Th2)‐type and Th2‐promoting cytokines, including interleukin‐4 (IL‐4), IL‐5, IL‐9, IL‐13, IL‐31, and thymic stromal lymphopoietin (TSLP); pro‐inflammatory cytokines, such as IL‐1β, IL‐12, IL‐17A, IL‐17F, IL‐23, and tumor necrosis factor (TNF); chemokine receptor CCR4; and lymphocyte surface and adhesion molecules, including CD2, CD11a, CD20, CD25, CD52, and OX40 ligand. In this task force paper of the Interest Group on Biologicals of the European Academy of Allergy and Clinical Immunology, we review biologicals that are currently available or tested for the use in various allergic and urticarial pathologies, by providing an overview on their state of development, area of use, adverse events, and future research directions.